IMPAKT OF THE VERTICAL DIMENSION OF OCCLUSION AND ARRANGEMENT OF TEETH ON SPEECH ARTICULATION (QUESTIONNAIRE STUDY) - Majed Hussein (Peytchinski Publishing, 2020)
Phonetic tests are one of the most important methods for the proper positioning of the teeth and identifying the vertical dimension of occlusion in denture fabrication. Purpose: Assessment of the level of awareness of dental practitioners and dental technicians regarding the impact of the vertical dimension of occlusion and the teeth arrangement on speech articulation. Material/Methods: 369 dental practitioners from 70 settlements (67 of which - towns and 3 - villages), and 84 dental technicians from 19 settlements (towns only) in Bulgaria were part of the research. The questionnaire study took 5 months (starting 2018). Results: The research results prove that speech function is influenced by both the vertical dimension of occlusion (opinion of 93.80 of the dental practitioners and 85.80 % of the dental technicians) and the arrangement of the artificial teeth (opinion of 94.80 of the dental practitioners and 91.70 % of the dental technicians). Conclusion:A high proportion of the inquired participants (over 90 %) admit the negative impact on the speech exerted by incorrect vertical dimension of occlusion and arrangement of teeth, and these are seen as a major factor for compromising the speech function.